Targeted Amplicon Sequencing for Single-Nucleotide-Polymorphism Genotyping of Attaching and Effacing Escherichia coli O26:H11 Cattle Strains via a High-Throughput Library Preparation Technique - Ison, Sarah A.; Delannoy, Sabine; Bugarel, Marie; Nagaraja, Tiruvoor G.; Renter, David G.; Bakker, Henk C. den; Nightingale, Kendra K.; Fach, Patrick; Loneragan, Guy H. (My University, 2016)
Enterohemorrhagic Escherichia coli (EHEC) O26:H11, a serotype within Shiga toxin-producing E. coli (STEC) that causes severe human disease, has been considered to have evolved from attaching and effacing E. coli (AEEC) O26:H11 through the acquisition of a Shiga toxin-encoding gene. Targeted amplicon sequencing using next-generation sequencing technology of 48 phylogenetically informative single-nucleotide polymorphisms (SNPs) and three SNPs differentiating Shiga toxin-positive (stx-positive) strains from Shiga toxin-negative (stx-negative) strains were used to infer the phylogenetic relationships of 178 E. coli O26:H11 strains (6 stx-positive strains and 172 stx-negative AEEC strains) from cattle feces to 7 publically available genomes of human clinical strains. The AEEC cattle strains displayed synonymous SNP genotypes with stx 2-positive sequence type 29 (ST29) human O26:H11 strains, while stx 1 ST21 human and cattle strains clustered separately, demonstrating the close phylogenetic relatedness of these Shiga toxin-negative AEEC cattle strains and human clinical strains. With the exception of seven stx-negative strains, five of which contained espK, three stx-related SNPs differentiated the STEC strains from non-STEC strains, supporting the hypothesis that these AEEC cattle strains could serve as a potential reservoir for new or existing pathogenic human strains. Our results support the idea that targeted amplicon sequencing for SNP genotyping expedites strain identification and genetic characterization of E. coli O26:H11, which is important for food safety and public health.